Nonlinearity in Market Efficiency: Comparison study of Malaysia, London and Singapore. - Azizan, Noor Azlinna; Brookfield, D. (2004)
It is argued that the efficiency in futures market depends on the nature of trading activity in futures and on its relation to the underlying security. Much of the studies in this are only focus on the linear relationship between this instruments and little has been done using the nonlinearity test.